Державна політика в галузі управління сферою професійно-технічної освіти: характеристика змісту та обґрунтування напрямів - Грень, Лариса Миколаївна (Видавничий дім "Гельветика", 2019)
У статті проаналізовано дисертаційні дослідження з формування та реалізації державної політики у сфері освіти України Є. Краснякова "Державна політика в галузі освіти в Україні: теоретико-історичний аспект" (25.00.01 – теорія та історія державного управління); М. Легенького "Адміністративно-правові засади формування та реалізації державної політики у сфері освіти"; В. Пономаренка "Дослідження та аналіз освітньої політики в Україні" (23.00.01 – теорія та історія політичної науки); М. Хитько "Стратегічне планування в системі державного управління освітою" (25.00.02 – механізми державного управління) та Н. Шульги "Державна освітня політика як інструмент соціально-економічного розвитку" (25.00.01 – теорія та історія державного управління). Розглянуто концептуалізацію змісту наукових поглядів щодо змісту поняття "державна освітня політика", конкретизовано зміст і напрями державної освітньої політики в галузі управління професійно-технічною освітою. Доведено, що вирішенню проблем, що стоять перед професійною освітою (зростання дефіциту робітничих кадрів на ринку праці України та низька соціально-економічна мотивація суспільства до здобуття професійних кваліфікацій; тенденція до погіршення показників України в міжнародних обстеженнях конкурентоспроможності й інноваційної привабливості, що впливає на економічний розвиток України; збільшення частки молоді, яка намагається здобувати вищу освіту, зокрема, за кордоном; втрата привабливості та престижності професійної освіти; зниження соціального статусу педагога професійної освіти), сприятиме виважена державна політика в галузі управління сферою професійно-технічної освіти. Розглянуто головні новації законопроєкту "Про професійну (професійно-технічну) освіту, які можна об’єднати у три блоки: 1. Забезпечення якості освіти. 2. Децентралізація управління та фінансування закладів. 3. Розвиток державно-приватного партнерства. Доведено, що напрями державної освітньої політики в галузі управління професійно-технічною освітою корелюють з основними напрямами державної освітньої політики України, що визначає реформування і модернізацію професійно-технічної освіти одним із найважливіших завдань освітньої політики держави: її відновлення, розвиток і виведення на рівень сучасних розвинених країн світу. Важливими перспективними напрямами щодо порушеної проблематики є обґрунтування специфіки державного управління розвитком системи професійно-технічної освіти на державному та регіональному рівнях.

The article analyzes dissertation researches on forming and realization of state policies in education sphere of Ukraine by the following authors: Ye. Krasniakov "State policies in the area of education in Ukraine: theoretic-and-historic aspect" (25.00.02 – theory and history of state management); M. Leghenky "Administrative and legal foundations of forming and realization of state policies in the sphere of education"; V. Ponomarenko "Research and analysis of education policies in Ukraine" (23.00.01 – theory and history of political science); M. Khytko "Strategic planning in the system of education’s state management" (25.00.12 – state management mechanisms) and by N. Shulga "State education policies as an instrument of socio-economic development" (25.00.01 – theory and history of public management). There are considered the conceptualization of scientific views’ contents regarding the essence of the notion of "state educational policy", clarifies the contents and directions of state educational policy in the sphere of vocation-and-technical training management. It is established that solving the problems facing vocational training in Ukraine (growing deficit of working professions employees in Ukraine’s labor market and low motivation on behalf of society to obtaining working qualifications; the tendency of worsening Ukraine’s positions in international researches of competitiveness and investment attractiveness that influence economic development of Ukraine; increase in the share of youths trying to obtain higher education, including those studying abroad; loss of attractiveness and prestige of vocational training; decrease in social status of a pedagogue in vocational training) will be enhanced by well-balanced state policies in the area of managing vocation-and-technical training sphere. There are viewed main novelties of the draft law "On vocational (vocation-and-technical) training" which can be grouped into the three blocks: 1. Ensuring training quality. 2. Decentralizing of management and financing of establishments. 3. Development of state-private partnership. It is proved that the directions of state educational policy in the sphere of vocation-and-technical training management correlate with the main directions of state educational policies of Ukraine that determines reforming and modernizing of vocation-and-technical training as one of the crucial goals of educational policies of the state: its renovation, development, and leading to the level of modern developed countries of the world. An important and perspective direction of the problematics in question is substantiation of peculiarities of vocation-and-technical training system’s state management at both the state and regional levels.
State policy in the area of vocation-and-technical sphere management: contents characteristic and directions’ substantiation
Keywords: навчальний процес; вища освіта; педагогічна діяльність; економіка; ринок праці; кадрова політика; право; state educational policies; vocation-and-technical training management; educational process; higher education; pedagogical activity; economics; law